Humulus lupulus Cone Extract Efficacy in Alginate-Based Edible Coatings on the Quality and Nutraceutical Traits of Fresh-Cut Kiwifruit - Katya Carbone; Valentina Macchioni; Greta Petrella; Daniel Oscar Cicero; Laura Micheli (MDPI AG, 2021)
In this work, an innovative coating strategy that is able to prolong the shelf-life of fresh-cut kiwifruit was proposed, and the effectiveness of the procedure was evaluated for a period of ten days under cold storage (4 °C). Alginate (2% m/v) functionalized with green extracts from hop (Humulus lupulus L.) cones (HE; 0.5 and 1%, v/v) was used as a coating material in order to assess the best performing strategy, leading to the most stable product. At the concentrations used to formulate the edible coatings, no contribution related to hop bitterness on the final product was recorded. The results were compared to control samples (without edible coating and coated only with alginate at 2% m/v). The plant extract was characterized by its main chemical traits and by 1H NMR profiling, revealing the presence of antioxidant and antimicrobial bioactive compounds (i.e., alpha and beta hop acids, xanthohumol). Furthermore, the characteristics of the samples during cold storage were evaluated by physico-chemical (i.e., weight loss, soluble solid content, titratable acidity, pH, color attributes) and nutraceutical (i.e., total polyphenol, ascorbic acid content, total carotenoids, chlorophylls) traits. The results showed that the incorporation of hop extracts into the edible coatings tested was able to preserve the quality and nutraceutical traits of fresh-cut kiwifruit during cold storage, thus prolonging their shelf life and marketability.